2015
DOI: 10.1371/journal.pone.0128583
|View full text |Cite
|
Sign up to set email alerts
|

Recovering More than Tree Cover: Herbivores and Herbivory in a Restored Tropical Dry Forest

Abstract: Intense and chronic disturbance may arrest natural succession, reduce environmental quality and lead to ecological interaction losses. Where natural succession does not occur, ecological restoration aims to accelerate this process. While plant establishment and diversity is promoted by restoration, few studies have evaluated the effect of restoration activities on ecological processes and animal diversity. This study assessed herbivory and lepidopteran diversity associated with two pioneer tree species growing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 50 publications
1
13
0
2
Order By: Relevance
“…We considered that the overall mean value of herbivory was not influenced by the occurrence of plants in restoration plots (i.e, a high density of plants). This is because other independent studies performed on the same study system, showed that herbivory levels were statistically similar between successional sites and restored plots (Hernández et al, 2014), or among different restoration treatments (with and without plantings; Juan-Baeza et al, 2015). In turn, the experimental design we used which was based on restoration plantings was successful in demonstrating inherent differences in herbivory correlated with successional status of plants, as it was shown in a large-scale restoration planting in Brazil, in which earlysuccessional species held higher herbivory than latesuccessional species (Massad et al, 2011).…”
Section: Speciesmentioning
confidence: 82%
“…We considered that the overall mean value of herbivory was not influenced by the occurrence of plants in restoration plots (i.e, a high density of plants). This is because other independent studies performed on the same study system, showed that herbivory levels were statistically similar between successional sites and restored plots (Hernández et al, 2014), or among different restoration treatments (with and without plantings; Juan-Baeza et al, 2015). In turn, the experimental design we used which was based on restoration plantings was successful in demonstrating inherent differences in herbivory correlated with successional status of plants, as it was shown in a large-scale restoration planting in Brazil, in which earlysuccessional species held higher herbivory than latesuccessional species (Massad et al, 2011).…”
Section: Speciesmentioning
confidence: 82%
“…Some authors argue that fencing against cattle should be sufficient to ensure forest recovery while others advocate for active interventions involving planting of native tree species (Aide et al, 2000; Gonzáez-Iturbe, Olmsted & Tun-Dzu, 2002; Burgos & Maass, 2004; Lebrija-Trejos et al, 2010). Recent investigations have found that fencing against cattle in a TDF of Southern Mexico was more important for lepidopteran recovery than planting (Juan-Baeza, Martínez-Garza & del-Val, 2015). However, active planting has been shown to speed up plant regeneration and lepidopteran arrival in other restoration experiences (Hernández et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…2). These can be broadly classified as: (1) resources, such as water (Reich and Borchert 1984;Chaturvedi et al 2013;Vadigi 2013;Barbosa et al 2014), light (Ceccon et al 2006;Tripathi and Raghubanshi 2014), and soil nutrients (Huante et al 1995;Ceccon et al 2006;Chaturvedi et al 2012;Tripathi and Raghubanshi 2014) and (2) disturbances, such as fire (Khurana and Singh 2001;Otterstrom andSchwartz 2006, Pluchon et al 2014), herbivory (Higgins et al 2000;Chaturvedi et al 2012;Norghauer and Newbery 2014;Juan-Baeza et al 2015;Torres and Renison 2015), grass competition (Riginos 2009;Ortega-Pieck et al 2011;Griscom et al 2014), and atmospheric CO 2 (Khurana and Singh 2002). A series of experiments have been conducted across the dry tropical environment, which suggest that tree-seedling survival and establishment are highly susceptible to water stress, nutrient shortage, shade, herbivory, and competition with grasses (Table 1).…”
Section: Resources and Disturbancesmentioning
confidence: 99%
“…For example, browsers have been observed to stimulate the shoot development under fertile soil condition (Du Toit et al 1990;Gerhardt 1998;Santiago et al 2012;Vadigi and Ward 2013), whereas grazers reduce grass competition and promote the seedling establishment (Briske 1996;Gunaratne et al 2010). Moreover, ungulate herbivores indirectly regulate the tree community structure and dynamics mainly by their excretal inputs enriching the soil nutrient status (Van der Waal et al 2011;Juan-Baeza et al 2015). Such externally added nutrient via herbivores on one hand promotes the growth of tree seedlings, whereas enhances the grass competition on the other and, thus, may reduce seedling establishment (Van der Waal et al 2009;Juan-Baeza et al 2015).…”
Section: Interactive Effects Of Herbivory Nutrient Addition and Gramentioning
confidence: 99%
See 1 more Smart Citation